Investigation of batch data flow transmission parameters - Tervydis, Paulius; Rindzevičius, Ramutis (Technological and Economic Development of Economy, 2006)
Rapid growth and increasing requirements for service quality, reliability, and efficiency have made traffic evaluation an essential consideration in design and operation of data transmission networks. In this paper we analyse performance measures of data transmission network servicing batch data flows. The article provides analysis of the one channel queuing system transmitting data packet flow general distributed. In this article we introduce queuing system with finite and infinite buffer capacity. In this article we analyse such data packets transmission performance parameters: average time spent by data packet in system, data packet delay variation, data packet loss. The data packet arrival rate and channel data packet transmission rate are independent of system state. A key mechanism of the proposed traffic model is that packet time spent in the system depends on channel utilization level, packet flow type and size of transmitted data. The proposed simulation model can be used when packet interarrival time follows such distributions: Pareto, Poisson, uniform, normal distribution. Simulation results of performance measures are defined by mathematical models. Considering simulation results recommendations were proposed to improve performance measures for batch data flow transmission over data networks. Pliūpsninio duomenų srauto perdavimo parametrų tyrimas Santrauka. Tiriama pliūpsninio duomenų srauto perdavimo duomenų perdavimo tinklais problema. Analizuojami pliūpsninio duomenų srauto, kurį generuoja atsitiktinis vartotojų skaičius, perdavimo vienu kanalu ypatumai. Atlikta analizė parodo, kad dėl vartotojų skaičiaus aktyvumo dinamikos laike jų sukuriamas atsitiktinis duomenų srautas yra pliūpsninis. Dėl tokio duomenų srauto pobūdžio atitinkamai priklauso ir pagrindiniai duomenų perdavimo parametrai: duomenų paketų perdavimo trukmė (vėlinimas), aritmetinis vėlinimo vidurkis, jo sklaida, paketų praradimas. Nustatyta, kad laikotarpiai tarp pliūpsninio duomenų srauto paketų ir jų perdavimo kanalu trukmės, atsižvelgiant į kanalo apkrovą, gali būti atsitiktinai pasiskirstę pagal eksponentinį, gama, Pareto, normalųjį ar kt. skirstinį. Pasiūlytas imitacinis modelis, kuriuo remiantis galima įvertinti tokio duomenų srauto perdavimo parametrų priklausomybes. Reikšminiai žodžiai: tinklas, duomenys, srautas, perdavimas, parametrai. First Published Online: 21 Oct 2010